Critical Validation: Black Women's Retention at Predominantly White Institutions. (August 2021) - Kelly, Bridget Turner; Raines, Alyscia; Brown, Rachel; French, Andrew; Stone, Joakina
Retention of Black students at predominantly White institutions (PWIs) is often studied. However, very few researchers examine what helped retain Black women undergraduate students from PWIs with multiple intersecting identities. Through a qualitative research design that honors the stories of 16 Black women who graduated from PWIs, we explore what helped to retain them at the PWI. Using Rendón's validation theory as a framework, we sought to understand how validating agents assisted in the retention of Black women undergraduate students. We provide implications for practice and practical suggestions on how PWIs can be more thoughtful about retention of this population.